Digital competency of Psychologists in Aotearoa New Zealand: A cross-sectional survey - Dobson, Rosie; Variava, Rushaina; Douglas, Meihana; Reynolds, Lisa M. (Frontiers in Digital Health, 2022)
Background The increasing implementation of digital health into psychological practice is transforming mental health services. Limited clinical resources and the high demand for psychological services, alongside the restrictions imposed on services during the global COVID-19 pandemic, have been a catalyst for significant changes in the way psychologists work. Ensuring Psychologists have the skills and competence to use these tools in practice is essential to safe and ethical practice. Aim This study aimed to explore the digital competence of psychologists working in Aotearoa New Zealand and their use of digital tools in the practice. Methods A cross-sectional online survey was conducted with Aotearoa New Zealand Registered Psychologists (n = 195) between July and November 2021. Results Participants reported varying degrees of competence across the digital tasks presented, with participants most commonly reporting moderate to high competence for engaging in remote supervision via digital means (86%) and obtaining client's informed consent for digital work (82%). In contrast, tasks that participants most reported not being moderately or highly competent in included working with interpreters remotely and evaluating the effectiveness and security of smartphone apps. Motivations to use digital technologies included meeting client preferences and needs, necessity for continuity of care, and the benefits of increased accessibility and reach. In contrast, the barriers to using digital technologies included client characteristics or preference, clinical factors, clinician preferences and skills, and workplace or technical issues or concerns. The majority (91.1%) were potentially interested in further training in this area. Conclusions The current study offers insights into the digital competencies of a workforce that has required rapid incorporation of technologies into professional practice over recent years. This snapshot of the digital skills of psychologists demonstrates a large variation in digital competence. In the current context, developing digital competencies seems a fundamental requirement for psychologists to work in ways that appropriately and safely deliver client-centred care.